The relationship between Malaysia crude oil prices, macroeconomic variables and the Islamic stock market in Malaysia: evident from FTSE bursa Malaysia emas shariah index / Norshila Mohd Zain - Mohd Zain, Norshila (Faculty of Business and Management, 2014)
This paper attempts to investigate the relationship between crude oil price, macroeconomic variables and the Islamic stock market in Malaysia. The independent variables are Malaysia crude oil price, Malaysia inflation rates and exchange rates of Ringgit Malaysia per US Dollar. The dependent variable is FTSE Bursa Malaysia Emas Shariah Index (FBMES). To identify the factors that affect the Islamic stock market performance in Malaysia, this study applied the Ordinary Least Square (OLS) method and Granger causality test using the monthly data over the period of January 2008 until January 2014. The OLS method results suggest that the crude oil price has a positive significant relationship with the FBMES prices while inflation rates and exchange rates have a positive but do not significant with the FBMES. The overall result of Granger causality test suggest that only exchange rates granger causes the Islamic stock prices while the Islamic stock prices only Granger causes inflation rate. Thus, OLS method suggests that factor affect FBMES the most is the Malaysia crude oil prices while Granger Causality Test suggests that the exchange rate of Ringgit Malaysia per US Dollar granger causes Islamic stock market in Malaysia.